Indikasi Terjadinya Predatory Pricing Terkait Kerjasama Grab Dengan Ovo Dalam Perspektif Hukum Persaingan Usaha - Ndaru Nadhi Hapsoro; A.M Hasan Ali; Fitriyani Zein (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThis study aims to examine the indications of violations according to Article 20 of Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition. In this case there are allegations from the online motorcycle taxi company Grab and the Ovo online financing transaction company that is alleged to violate the unfair business competition provisions. There are indications of payment that does not make sense in using ovo when paying a grab rate of one rupiah. This study uses a type of empirical and qualitative juridical research. The results showed that no violations were found because there were no dead companies and Grab and Ovo were not in a dominant position and did not make them dominate the competitive market. Although basically the price of one rupiah is considered below the minimum price and can cause violations.Keywords: Predatory Pricing, Indications, Business Competition